Genome-wide siRNA screening in mouse bone marrow-derived macrophages revealed that knockdown of ribosomal proteins suppresses IL-10 and enhances TNF-α production. - Okamura, Yoshihiko (J Clin Exp Hematop, 2018)
Macrophages play a central role in the immune response, and their diverse functions are attributed to the spectrum of their functional states. To elucidate molecules involved in modulating the balance between the anti-inflammatory cytokine IL-10 and the pro-inflammatory cytokine TNF-α, we conducted genome-wide siRNA screening. First, we established an siRNA screening system using mouse bone marrow-derived macrophages, which are a suitable model for studying functional states of macrophages in vitro. In the primary screen and the subsequent reproducibility assay, 112 siRNA pools demonstrated enhancement of IL-10 production and 497 siRNA pools suppressed IL-10 production. After a deconvolution assay for IL-10-up-regulating siRNA pools, 8 genes were identified as IL-10 repressors, including Cnot1 and Rc3h1, components of the CCR4-NOT complex known to degrade cytokine mRNAs. On the other hand, siRNA pools targeting ribosomal proteins were frequently found among those that down-regulated IL-10 production and up-regulated TNF-α production. Four pools were assayed using deconvoluted siRNAs and identified as high-confidence hits. Thus, we found that the genome-wide knockdown of 19 ribosomal proteins resulted in decreased IL-10 and increased TNF-α production.